Clinical Effects of Edaravone in Stroke: A Review - Thomas, Anisha; Solomon, Anuja; MN, Tanushree; Arjun, Akhila S (Indian Journal of Pharmacy Practice)
Edaravone, a free radical scavenger, is the only neuroprotective agent for ALS. Free radicals play a crucial role in brain ischemic injury by exacerbating membrane damage through peroxidation of unsaturated fatty acids of cell membrane, leading to neuronal death and brain edema. Free radicals have been implicated in stroke pathophysiology as pivotal contributors to cell injury. After brain damage, caused by either ischemic or hemorrhagic stroke, physiological systems involved in the removal of the excess of free radicals are impaired and the formation of free radicals is increased. This study aims to evaluate the safety and efficacy of edaravone, a novel free radical scavenger, in a group of Indian patients of acute ischemic stroke. However, its actions on pro-inflammatory responses under stroke are still understudied. This data suggests that free radical scavengers may reduce systemic inflammatory responses under acute stroke conditions and therefore, oxidative stress can be still a viable target for acute stroke therapy. Efficacy of edaravone range from large significant clinical improvements to only modest improvements in clinical function measured using standard stroke scales when administered 6-72 h following an ischemic stroke. With almost 17 years of edaravone clinical experience, a few adverse events including acute renal failure have been noted. Edaravone treatment was safe and effective in providing early and sustained neurological improvement in patients with acute ischemic stroke.
Keywords: Edaravone; Stroke; Free radical; ALS; Neuroprotective; Ischemic stroke.